2020
DOI: 10.1371/journal.pone.0238630
|View full text |Cite
|
Sign up to set email alerts
|

The use of embryonic chicken eggs as an alternative model to evaluate the virulence of Salmonella enterica serovar Gallinarum

Abstract: Salmonella enterica serovar Gallinarum ( S . Gallinarum) can cause fowl typhoid, a severe systemic disease responsible for considerable economic losses. Chicken pathogenicity test is the traditional method for assessing the virulence of S . Gallinarum. However, this method is limited by several factors, including ethical considerations, costs, and the need for specialized facilities. Hence, we established a chicken embryo lethality assay (ELA) model to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…SE_TAU19 achieved a 100% mortality rate compared to a virulent APEC strain which achieved an 80% mortality rate (Figure 2). SE_TAU19 virulence to broiler embryos was found to be comparable to published embryo lethality in Salmonella enterica serovar Gallinarum infections (56). This approach may be useful for future SE virulence or vaccine development studies.…”
Section: Discussionmentioning
confidence: 57%
“…SE_TAU19 achieved a 100% mortality rate compared to a virulent APEC strain which achieved an 80% mortality rate (Figure 2). SE_TAU19 virulence to broiler embryos was found to be comparable to published embryo lethality in Salmonella enterica serovar Gallinarum infections (56). This approach may be useful for future SE virulence or vaccine development studies.…”
Section: Discussionmentioning
confidence: 57%
“…Previous study has reported that the magnolol exerted a low cytotoxicity in broilers, which can improve growth performance by modulating mucosal gene expression and the gut microbiota in the treatment of 300 mg/kg ( Chen et al., 2021 ). Chicken embryos were used as an infection model to evaluate the protection provided by magnolol as previously described with some modifications ( Helmy et al., 2020 ; Zhang et al., 2020 ). Briefly, Specific pathogen-free (SPF) chicken embryos were purchased from Merial-Vital, Beijing, China, and hatched in an environment of 37.5°C and 50–60% humidity.…”
Section: Methodsmentioning
confidence: 99%
“…The treated chickens were observed twice a day for 2 weeks after administration. Clinical scores were determined and recorded using a system as we have previously described ( 25 ). Briefly, disease severity was scored as follows: 0, normal; 1, depression and ruffled feathers; 2, depression, ruffled feathers, and respiratory distress; 3, abovementioned clinical signs plus anorexia, emaciation, and green-yellowish diarrhea; and 4, death.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of this period, all surviving chickens were euthanized. Clinical scores were determined and recorded following the method previously described ( 25 ).…”
Section: Methodsmentioning
confidence: 99%